Possible amphi-Atlantic dispersal of Scyllarus lobsters (Crustacea: Scyllaridae): molecular and larval evidence - Genis-Armero, Rebeca; Guerao, Guillem; Abelló, Pere; González-Gordillo, J. Ignacio; Cuesta, José A.; Corbari, Laure; Clark, Paul F.; Capaccioni-Azzati, Romana; Palero, Ferran (Zootaxa, 2017)
DNA methods may contribute to better understand larval dispersal of marine lobsters. The molecular analysis of phyllosoma specimens from the East Atlantic facilitated for the first time here the description of Scyllarus subarctus Crosnier, 1970 larvae. The identification of S. subarctus phyllosomae from Cabo Verde confirmed that this species has a much wider geographic distribution than previously thought. Moreover, the phylogenetic analyses placed S. depressus from the Western Atlantic together with the African species S. subarctus, instead of other American Scyllarus. In fact, S. depressus and S. subarctus formed a strongly supported clade with comparatively low genetic differentiation, suggesting the possibility that they might be recently-diverged sister taxa with an amphi-Atlantic distribution. Support for this is provided by the examination of S. subarctus larvae and the lack of any qualitative character that would allow for differentiation between the adults of S. subarctus and S. depressus. The results obtained highlight the challenges of current Scyllarus systematics and the need for further research on Atlantic slipper lobsters.